2003
DOI: 10.1177/1099800403257166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morphine and Time of Day on Pain and Beta-Endorphin

Abstract: Clients report more pain at some times of day than at others due, in part, to the temporal variation of the body's inhibitory pain response. The analgesic effectiveness of morphine varies with the time of day, perhaps due to the inhibiting or enhancing effects of the drug on plasma beta-endorphin (BE). This experiment was designed to examine the timed effects of morphine on the pain-induced BE response. Six groups of treatment mice (injected with morphine sulfate) and 6 groups of control mice (injected with sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…It has been reported that diurnal animals, including man, are less sensitive to pain during day time (Rigas et al, 1990; Göbel and Cordes, 2005) whereas the opposite seems to be the case in nocturnal animals (Kavaliers and Hirst, 1983; Kavaliers et al, 1984; Yoshida et al, 2003). The time-of-day-related variations in pain sensitivity have been attributed to circadian variations in endorphin synthesis (Kavaliers and Hirst, 1983; Rasmussen and Farr, 2003). However, they may also reflect diurnal variations in LC activity: in diurnal animals the LC is maximally active during day time, and LC activity is known to be associated with an analgesic effect (see section “Processing of Pain by the LC,” above).…”
Section: Pupillary Light Reflexmentioning
confidence: 99%
“…It has been reported that diurnal animals, including man, are less sensitive to pain during day time (Rigas et al, 1990; Göbel and Cordes, 2005) whereas the opposite seems to be the case in nocturnal animals (Kavaliers and Hirst, 1983; Kavaliers et al, 1984; Yoshida et al, 2003). The time-of-day-related variations in pain sensitivity have been attributed to circadian variations in endorphin synthesis (Kavaliers and Hirst, 1983; Rasmussen and Farr, 2003). However, they may also reflect diurnal variations in LC activity: in diurnal animals the LC is maximally active during day time, and LC activity is known to be associated with an analgesic effect (see section “Processing of Pain by the LC,” above).…”
Section: Pupillary Light Reflexmentioning
confidence: 99%
“…A hot-plate (15.9 × 15.9) insulated with polystyrene (Thermolyne Aluminum Type, Model HPA1915B, Dubuque, IA) was maintained at 55 ± 1 • C by a temperature controller (GlasCol, PowrTrol Model, Terre Haute, IN) and monitored using a thermo-coupled thermometer (Omega, Model HH11, Stamford, CT). In order to confirm that pain had been experienced by exposure to the hot-plate, the animal's paw-licking response was observed (Pierretti et al, 1993;Rubenstein et al, 1996;Liang et al, 2003;Rasmussen and Farr, 2003;Vermeirsch and Meert, 2004;Wesolowska et al, 2004;Suaudeau et al, 2005;Altug et al, 2006;Berrocoso et al, 2006;Smith and Lindsay, 2007;Hsieh et al, 2008;Milano et al, 2008). Exposure of a mouse to a 55 • C hot-plate induces the paw-licking response and the mouse begins to lick its front or hind paws.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Although there is evidence suggesting that BE is released rhythmically and episodically (Butler et al, 1989;Iranmanesh et al, 1989;Veldhuis et al, 1990;Rasmussen, 2000;Rasmussen and Farr, 2003;), little detail has been provided describing the role of sample timing in response to pain and stress. Standardized methods could be used if they were developed and tested.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cut-off time should be selected carefully to obtain sufficient responses without causing tissue damage. For the hot-plate test, cut-off latencies have previously been selected as 30 s or 45 s [13,32,33], 120 s [12,34], and 60 s or 80 s [35][36][37]. In this study, the cut-off latency was eventually set at 80 s for morphine, fentanyl and tramadol, and 60 s for the other 3 narcotics.…”
mentioning
confidence: 99%